Bentuk Kerjasama Anak Usia 4-6 Tahun Melalui Permainan Tradisional Sen Di Desa Kufar Kabupaten Seram Timur - Saadia Buaklofin; Umi Kusyairy; M Yusuf Tahir (NANAEKE: Indonesian Journal on Early Childhood Education, 2023)
The research aims to determine the application of traditional sen games in Kufar Village, East Seram Regency, determine forms of cooperation in children aged 4-6 years through traditional sen games in Kufar Village, East Seram Regency, and determine the factors inhibiting forms of cooperation in children aged 4-6 years. 6 years through the traditional game of sen in Kufar Village, East Seram Regency. The research method is descriptive qualitative. Observation, interview, and documentation techniques were applied to 10 children selected using purposive sampling techniques. The results of the research are: (1) the application of the traditional sen game works well and has a significant effect on children in collaborating with their friends; (2) the forms of cooperation in children aged 4-6 years through traditional sen games are very diverse, namely: (a) spirit of togetherness and team cohesion, (b) not giving up easily, (c) self-control, (d) learning to focus and (e ) sportsmanship; and (3) factors inhibiting forms of cooperation, namely: (a) lack of parental support, (b) less conducive environment (c) lack of play area and (d) use of gadgets. The research implies that children aged 4-6 years must be given an understanding of the positive impact of traditional sen games so that they are serious about playing. Parents and teachers play an important role in forming children to work together with their friends. As well as variables, research methods, and media are expected to be more varied.